The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.sbspro.2014.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating a New Doctoral Nursing Program: A Jordanian Case Study

Abstract: Establishing and maintaining a quality nursing doctoral program in a country with limited resources is a challenge to program managers. Continuous evaluation is essential to pinpoint areas of improvement. This study aims to evaluate a nursing PhD program from the perspective of its first graduate cohort to provide feedback for improvement. Qualitative design using focus group method was used to collect data from a purposive sample of graduates (N=14). Content analysis revealed seven themes: Opportunity to earn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…If the doctoral program fails to meet students' expectations, the program is seen as a continuation of their MSN education (Özdemir et al, 2014). Students participating in the study of Nabolsi et al (2014) on doctoral nursing programs in Jordan stated that they would like to have elective courses that help them to develop and prepare for different roles in the future. National and international cooperation is also identified as a factor in improving the quality of a program.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the doctoral program fails to meet students' expectations, the program is seen as a continuation of their MSN education (Özdemir et al, 2014). Students participating in the study of Nabolsi et al (2014) on doctoral nursing programs in Jordan stated that they would like to have elective courses that help them to develop and prepare for different roles in the future. National and international cooperation is also identified as a factor in improving the quality of a program.…”
Section: Discussionmentioning
confidence: 99%
“…Anderson (2000) described five components related with the quality of doctoral education: faculty, students, research, program, and career development. Recent studies investigate the views of students and faculty members about the quality of doctoral education Kim et al, 2006;Kim et al, 2010;Kim et al, 2012;Kim et al, 2015;Kim, Park, Park, Khan, & Ketefian, 2014;Kjellgren, Welin, & Danielson, 2005;Mckenna, Keeney, Kim, & Park, 2014;Nabolsi, Abu-Moghli, & Khalaf, 2014;Nagata et al, 2012, Park, Kim, & Kyung, 2013Smith & Delmore 2007).…”
mentioning
confidence: 99%
“…In 1953 a ministry of health school of nursing was opened, and in 1962 the Princess Muna College of Nursing was opened and university education for nures commenced in the University of Jordan in 1972(Zahran, 2011. Masters programmes only commenced in 1986 with faculty being Jordanians with masters or PhDs from foreign universities (Nabolsi et al, 2014). The cost and difficulty for Jordanians with family commitments made locally run programmes attractive (Nabolsi et al, 2014) and in 2005 the first PhD nursing programme started at the University of Jordan (Zahran, 2011).…”
Section: Kingdom Of Jordanmentioning
confidence: 99%
“…The literature identifies factors associated with quality in nursing doctoral programmes, including supportive academic learning environments, faculty who provide supervision and support and who are active scholars and leaders in their fields of expertise, as well as the availability of resources (Evans and Stevenson, 2011;Minnick et al, 2010;Minnick et al, 2017;Nabolsi et al, 2014;Volkert et al, 2018). Moreover, such programmes should be staffed with doctorally prepared nursing faculty who can provide high-quality mentorship to prepare the next generation of nurse scientists (Smeltzer et al, 2015).…”
mentioning
confidence: 99%
“…In a recent Turkish study, Kapucu and Bulut (2019) found that the curriculum, academic personnel, and academic environment were major factors affecting the quality of nursing doctoral education. While the continual evaluation of nursing doctoral programmes is an important element in supporting their long-term success (Nabolsi et al, 2014;Kapucu and Bulut, 2019), the literature raises concerns about the lack of a coherent instrument to systematically evaluate the quality of nursing doctoral education worldwide (Molzahn and Clark, 2015). Background Three decades ago, the Educational Testing Service, the world's largest private nonprofit educational testing and assessment organization, used the Graduate Program Self-Assessment (GPSA) questionnaire to evaluate the quality of doctoral education in the disciplines of nursing, history, and psychology in the United States (Chambers and Holzemer, 1988).…”
mentioning
confidence: 99%